2020
DOI: 10.1186/s12879-020-05622-2
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Leishmania spp. infection among HIV-infected patients living in an urban area in Brazil: a cross-sectional study

Abstract: Background There is little information about the frequency of Leishmania infection in asymptomatic people living with HIV (PLWH) and about the performance of laboratory diagnostic methods in coinfected patients in Latin America. The main objective of this study is to evaluate the frequency of Leishmania spp. infection in HIV-infected patients living in an urban area in Brazil. Methods To detect Leishmania infection, diagnostic tests were performed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…These samples came from patients born in the state of São Paulo, which for decades has presented several municipalities and endemic regions with both CD and leishmaniasis. Cunha et al [23] using the same samples showed positivity for Leishmania infection in these same three ELISA-positive/TESA Blot-negative samples in our cohort. So, we believe only two samples were truly positive for CD, with a prevalence of 0.83%.…”
Section: Discussionsupporting
confidence: 82%
“…These samples came from patients born in the state of São Paulo, which for decades has presented several municipalities and endemic regions with both CD and leishmaniasis. Cunha et al [23] using the same samples showed positivity for Leishmania infection in these same three ELISA-positive/TESA Blot-negative samples in our cohort. So, we believe only two samples were truly positive for CD, with a prevalence of 0.83%.…”
Section: Discussionsupporting
confidence: 82%
“…Notably, leishmaniasis is of much greater risk to IS populations, including HIV-positive individuals, SOT recipients, and patients under treatment with immunosuppressive drugs. HIV/ Leishmania co-infections more often lead to clinical VL, and with greater severity [ 117 , 120 ]. Indeed, it has previously been demonstrated that HIV-infected individuals with asymptomatic Leishmania infection may transmit the parasite to sand flies, leading to further spread of infection [ 63 , 121 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, other studies have described the high prevalence of Leishmania spp. infections in immunosuppressed people 8 , 9 , including HIV/CL 10 and HIV/DCL 11 coinfections in Maranhao State.…”
Section: Introductionmentioning
confidence: 99%